Perfil dos glicosaminoglicanos, morfologia do sistema reprodutor feminino e desenvolvimento pós-implantacional em cutias (Dasyprocta leporina Linnaeus, 1758) - Oliveira, Gleidson Benevides de (Universidade Federal Rural do Semi-Árido, 2016)
The morphological knowledge and data about the composition of glycosaminoglycans (GAGs) in the female reproductive system and placental of agouti are essential to the understanding of reproductive events. In addition to these, the knowledge of embryonic and fetal development in the specie, provides as the basis for application of ultrasound examination and reproductive biotech, contributing directly to conservation of the specie and commercial exploitation. Therefore, the objective describe the anatomohistological characteristics of the reproductive tract of agoutis females, as well as identify the profile of glycosaminoglycans in reproductive organs and placenta during the pregnancy. Were utilized agoutis 25 adult females at different stages of the estrous cycle and pregnancy, obtained in Centre of Multiplication of Wild Animals of the Universidade Federal Rural do Semi-Árido. After eutanasiados, abdominal and pelvic cavities were opened, the reproductive organs and fetuses when gifts were photographed in situ and ex situ and analysed to morphometric. Each body fragments were fixed in 4% paraformaldehyde solution and 2.5% glutaraldehyde and submitted to histological technique of light and scanning electron microscopy. Fragments of organs were also placed in acetone to remove the lipids and then the sample subjected to agarose gel electrophoresis. Blades for light microscopy, were stained with hematoxylin-eosin, Gomori stain, Alcian-Mallory and Periodic Acid Schiff (PAS). It was observed that he ovary of the Dasyprocta leporina is coated by simple cubic to squamous epithelium that rests on the tunica albuginea, showing a cortical and medular zone. The uterine tube is organized in three layers, a mucous membrane (simple ciliated columnar epithelium), the lamina propria (loose connective) and serosa. The villus height and muscle layer thickness varying between the areas of infundibulum, isthmus and ampulla. In pregnancy this organ has profile variable, with predominance of dermatan sulfate (DS) and heparan sulfate (HS) in early gestation and DS and chondrotin sulfate (CS) in the middle and final thirds with sharp reduction at term. The uterus is classified as partial double, consisting of two horns and a cervix with two distinct ostia that communicate with the body and a single ostium that opens into the vagina. The uterine horn presented throughout pregnancy a predominance of CS and DS, with small amount of HS. The vagina has three layers, the outer adventitia (connective tissue), muscular and mucous membrane composed of epithelium that varies from little pavimentoso storied without keratinization (luteal phase) the storied pavimentoso keratinized and cornified (follicular phase) enough frilled and with leukocytes cells. In the vagina, the main GAG found was the DS, with small concentration of HS analyzed throughout of the pregnancy. The vulva is located between the anus (dorsal) and the ostium and the vestibule urethral absent in the species. The clitoris is external to vagina, in which in its peak protrude sideways two spicules corneas and the urethra centered, in the absence of a common part between the urinary and genital tracts. Embryos at 30 days after copulation had form of "C" with limb buds paddle-shaped, Crown-Rump (CR) of 10.75 ± 0.11 mm and weight of 0.17 ± 0.03 g; 40 days the skin was smooth and transparent and liver boss and curvature of reduced body, CR 19.5 ± 0,007 mm and weight 1.34 ± 0.01 g; after 65 days, the genital tubercle was already differentiated and CR was 83 ± 0.08 mm and weight of 29.22 ± 0.46 g; 85 days, presence of stubble throughout the body, eyes partly open, CR of 127.7 ±0.6 mm and weight of 96.56 ± 7.37 g; 100 days, mature fetus with long hair and the whole body, fully formed tooth and nail and open auditory meatus, CR was 164.3 ± 10.4 mm and weight of 166.5 ± 7.79 g; the infants had the open eyes and bristling at birth, with CR 179.1 ± 0.5 and weight of 201.88 ± 1.89 g. Concluded that the profile and concentration of GAGs varies as to the organ and gestation period and that the age of the embryo/fetus can be evaluated during pregnancy, allowing to estimate gestational age and the data can be used as parameters to ultrasound examinations, helping in the identification of diseases throughout development
Keywords: Ciclo estral; Gestação; Feto; Hormônios ovarianos; Matriz extracelular; Roedor; Estrous cycle; Extracellular Matrix; Fetuses; Ovarian hormones; Pregnancy; Rodent; CIENCIAS AGRARIAS::MEDICINA VETERINARIA